Tantangan Bangunan Ilmu Profetik: Teoritis dan empiris - Indartono, Setyabudi (Universitas Negeri Yogyakarta, 2015)
Islam is believe as a perfect system. It roles all of the aspect of human life. However few scientists are presented to explore a lot of science paradigm based on religion. It is proposed that the progress of science based positivism is theoretically failed. Further scholars suggest that the finding of empirical study of science based positivism is heading a huge of global problem if human life and its environment. Accordingly, this study propose that scholars should investigate and explore various aspect of knowledge and science based on religion or prophetics based.